The Effect of World Oil Prices, Silver Prices, Exchange Rates, Dow Jones Industrial Average, on the SRI Kehati Index on the Indonesia Stock Exchange for the period January 2021–December 2021 - VIVIN HANITHA; Marselia Purnama; Octavianti Purnama (eCo-Buss, 2022)
Currently, awareness of the importance of environmental sustainability is a trend that is carried out by many countries in the world with the term Go Green. Awareness of Importance protecting the environment is currently supported by the publication of public policies related to this matter. So that the SRI Kehati Index was formed in 2009. This study focuses on the object of research the influence of world oil prices, silver prices, USD exchange rate, the Dow Jones Industrial Index on the SRI Kehati Stock Price Index in the period January 2021 to December 2021, and obtained a total of 247 data. The method chosen for this research is the Ordinary Least Square method with classical assumption test, f test, t test, multiple linear regression analysis, and coefficient of determination test. The test results conclude that partially oil prices, silver prices, the Dow Jones index and the USD exchange rate have a significant influence. Simultaneously. Oil prices, silver prices, the Dow Jones index and the USD exchange rate were tested together against the Y variable, namely the SRI Kehati Index. With adjusted results 0.424210 or 42.42% while the rest is shown in the variables not examined in this study.